Analysis on the potential performance of GPS and Galileo Precise Point Positioning using simulated Real-Time products - Basile, Francesco; Moore, Terry; Hill, Chris (2017)
With the evolving Global Navigation Satellite System (GNSS) landscape, the International GNSS Service (IGS) has started the Multi-GNSS Experiment (MGEX) to produce precise products for new generation systems. Various Analysis Centres are working on the estimation of precise orbits, clocks and bias for Galileo, Beidou and QZSS satellites. However, at the moment this products can only be used for post-processing applications. Indeed the IGS Real-Time service only broadcasts GPS and GLONASS corrections. In this research, a simulator of Multi-GNSS observations and Real-Time precise products has been developed to analyse the performance of GPS only, Galileo only and GPS plus Galileo Precise Point Positioning. The error models in the simulated orbits and clocks were based on the difference between the GPS Real-Time and the Final products. Multiple scenarios were analysed, considering different signal combined in the Ionosphere Free linear combination. Results in a simulated open area environment show better performance of the Galileo only case over the GPS only case. Using the two systems together provides good improvements, in particular in the convergence time. This paper will also consider the impact of different linear combinations of the Galileo signals, and the potential of the E5 AltBOC signal. Finally alternative methods of ionosphere error mitigation are considered in order to ensure the best possible positioning performance from the Galileo E5 signal in multi-frequency PPP.